PRESENCIA DEL PEZ LUNA MOLA MOLA (LINNAEUS, 1758) (PISCES: MOLIDAE) EN EL DEPARTAMENTO DEL MAGDALENA, CARIBE COLOMBIANO (Boletín de Investigaciones Marinas y Costeras, 2016)
Information about the ocean sunfish, Mola mola (Pisces Molidae), coming from an individual captured off Los Cocos, northeast Magdalena Department, is presented.